Nontoxic: Masculinity, Allyship, and Feminist Philosophy - Almassi, Ben (Springer Nature, 2022)
This open access book argues for allyship masculinity as an open-ended, intersectional model for feminist men. It provides a roadmap for navigating between toxic masculinity on one side, and feminist androgyny on the other. Normative visions for what men should be take many forms. For some it is love and mindfulness; for others, wildness and heroic virtue. For still others the desire to separate a healthy manhood from toxic masculinity is a mistake: better to refuse to be men and salvage our humanity. Though Ben Almassi challenges the visions that Mary Wollstonecraft, bell hooks, and others have offered, he shares their belief that masculinity can be grounded in feminist values and practices. Almassi argues that we can make sense of relational allyship as practices of feminist masculinity, such that men can make distinctive and constructive contributions to gender justice in the unjust meantime.